Effectiveness of video-based home exercise program on physical activity and glycemic control in patients with type 2 diabetes mellitus - Asnuddin Asnuddin; Adillah Nurfatiyah; Sulaeman Sulaeman; Meriem Meisyaroh Syamson (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder characterized by persistent hyperglycemia and is frequently associated with low levels of physical activity. Limited access to structured exercise programs remains a major barrier to optimal diabetes management, particularly in primary healthcare settings. Video-based home exercise programs offer a practical and accessible approach to promoting physical activity and improving glycemic control. This study aimed to evaluate the effectiveness of a video-based home exercise program on physical activity levels and fasting blood glucose among patients with T2DM. Research Methodology: A quantitative quasi-experimental study with a one-group pretest–posttest design was conducted among 30 patients with T2DM at a primary healthcare facility. Physical activity was assessed using the International Physical Activity Questionnaire (IPAQ), while fasting blood glucose levels were measured before and after the intervention. Data were analyzed using the Wilcoxon Signed Ranks Test and paired t-test, with statistical significance set at p < 0.05. Results: The intervention resulted in a significant increase in physical activity levels (Z = –4.704; p = 0.000). In addition, mean fasting blood glucose levels decreased significantly from 172.60 ± 29.41 mg/dL to 151.87 ± 27.83 mg/dL (t = 2.665; p = 0.012). Conclusion: The video-based home exercise program was effective in improving physical activity and glycemic control among patients with T2DM. This intervention is a feasible, low-cost strategy to support diabetes self-management in primary healthcare settings